Quality and Impact in Global Education Empirical and Conceptual Perspectives for Planning and Evaluation - Bergmüller, Claudia (Erziehungswissenschaft und Weltgesellschaft, 2021)
For several years now, the demand for increased impact orientation has also affected the field of Global Education (GE) / Development Education and Awareness Raising (DEAR). In this context, a vivid discussion is still ongoing regarding what can be considered an ›impact‹ in GE/DEAR and how these impacts can be analysed. Both questions are dealt with within the scope of the research project ›Impacts and methods of impact monitoring in development education and awareness raising‹, which was financed by the German Federal Ministry for Economic Cooperation and Development (BMZ) and which is to be presented in this volume. Against the backdrop of the empirical findings of this research project, this publication shows which effects can be targeted in the planning and evaluation of GE-/DEAR-projects and which contextual conditions can influence their effectiveness.